Economic Evaluation of Waste Management and Environmental Performance in SMEs Using GRI 300 - Sara Marlyn Paru; Hesty Theresia Salle (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Waste is commonly defined as the residual output of production processes, which varies across industrial sectors depending on operational activities. Small-scale food industries, including tofu and tempeh manufacturing, generate significant solid, liquid, and gaseous waste that may contribute to environmental pollution if not properly managed. This study aims to identify, measure, and analyze operational activities and waste management practices using the GRI 300 environmental performance standard at the tofu and tempeh manufacturing SME in Jayapura Regency. The research employs a qualitative case study approach to obtain an in-depth understanding of sustainability practices within business operations. The findings reveal that sustainability implementation remains limited and has not been systematically integrated into operational management. The use of materials, energy, and water occurs at a relatively high level without adequate recording, measurement, and evaluation systems, limiting the ability to assess resource efficiency and environmental impact reduction. In conclusion, the enterprise has not yet optimally implemented structured environmental management practices, indicating the need for systematic monitoring, reporting mechanisms, and improved sustainability strategies to enhance environmental performance and operational efficiency.